A folded filter element based on PTFE modified separation membrane with high efficiency interception and preparation method thereof
By using the lifting molding process of efficiently intercepted PTFE-modified separation membrane and biomass carbon fiber carrier in the folding filter element, the existing filter element has been solved, and the effects of high filtration accuracy, anti-fold fatigue and long service life are achieved, which is suitable for efficient treatment of industrial waste gas.
Patent Information
- Application Number
- CN202311582127.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-11-24
AI Technical Summary
The existing folding filter element has a small thickness, limited filtering capacity, short service life, and is prone to aging and blockage in high temperature or humid environments, making it difficult to be suitable for efficient treatment of industrial waste gas.
A modified separation membrane based on efficient retention was used to prepare a biomass carbon fiber carrier by hydrothermal carbonization treatment of biomass materials, and placed it in molten PTFE for lifting and forming to form a self-supported crude film. Subsequently, the crude film is impregnated with reacting monomer and heat treatment to form a folded filter element with high filtration accuracy and anti-fold fatigue.
It realizes the high filtration accuracy, folding fatigue resistance and long service life of the filter element. It is suitable for industrial waste gas treatment in high temperature or humid environments, significantly improving the actual service life and filtering performance of the filter element.
Smart Images

Figure CN118477491B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation membranes, and in particular relates to a folded filter element based on a PTFE modified separation membrane with high efficiency interception and a preparation method thereof. Background Art
[0002] Since PTFE has good hydrophilicity, chemical corrosion resistance, high temperature resistance, strong acid and alkali resistance, etc., it can be used for sterile air intake filtration, respiratory filtration, sterilization filtration of high-purity gas or compressed air in the electronics industry, and sterilization filtration of organic solvents. The filter element prepared based on the high-porosity PTFE membrane can filter all dust particles including bacteria while maintaining air circulation, thereby achieving the purpose of purification and ventilation.
[0003] Patent CN101961607A discloses a folded polytetrafluoroethylene composite microporous filter element, wherein the core filter layer is composed of a polytetrafluoroethylene composite membrane, the pre-filter layer is composed of two layers of polyester non-woven fabrics, and the support layer is composed of a layer of polyester non-woven fabric and a layer of polypropylene mesh structure overlapping each other. The polytetrafluoroethylene composite membrane is used as a filter membrane, and the polyester non-woven fabric on the upstream side and the polyester non-woven fabric and polypropylene mesh structure on the downstream side ensure the mechanical strength of the filter element, increase the dust and dirt holding capacity of the filter element, and the low-gram polyester non-woven fabric and polypropylene mesh structure optimize the fluid flow channel of the filter element, increase the air flux, and reduce the fluid resistance. However, the general process for preparing PTFE separation membranes will compound PTFE on substrates such as paper and non-woven fabrics for application, resulting in the comprehensive performance of the separation membrane being limited by the substrate. When multiple layers of carbon cloth are stacked, the thick film prepared by using carbon cloth as a carrier has interface defects. For example, carbon cloth has a certain brittleness after carbonization, and the folding part of the filter element is prone to aging and cracking, which destroys the support of the three-dimensional skeleton structure of the carbon cloth. Therefore, it is urgent to develop a folding filter element that is resistant to folding and aging. In addition, the existing filter element is not suitable for operation at high temperatures. When the water content in the dust exceeds 25%, the dust is easy to adhere to the outside of the filter screen, making it difficult to clean the dust, increasing the flow resistance, and causing the filter material to fail and damage prematurely.
[0004] Earlier, the researchers of this application developed the corresponding bio-based filter membrane and successfully produced a graded porous filter membrane with high thickness, high retention rate and long service life. However, when the filter membrane was folded into a fin-type structure filter element, it was found that folding fatigue was prone to occur during the folding process. This may be due to the local rigidity of its microstructure and the excessively high elastic modulus, which led to the folding of the folded structure and the collapse of the folded part, as well as the breakage of some three-dimensional network fiber structures, resulting in poor effect when the filter membrane was simply folded into a filter element. Summary of the invention
[0005] In order to solve the problems that the existing foldable filter element has a small thickness and a limited actual filtration volume, resulting in a short actual service life of the filter element, and simply thickening the filter membrane is more prone to clogging, which also leads to a limited service life, and the bio-based template filter membrane previously studied has defects in folding and use, the present invention provides a foldable filter element based on a PTFE modified separation membrane with high-efficiency retention, and a method for preparing the foldable filter element.
[0006] The objects of the present invention are:
[0007] 1. Ensure that the filter element has a high filtration accuracy;
[0008] 2. Enhance the filter element's anti-folding fatigue resistance;
[0009] 3. Extend the actual service life of the filter element.
[0010] To achieve the above objectives, the present invention adopts the following technical solutions.
[0011] A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception,
[0012] The method comprises:
[0013] 1) taking a biomass material and subjecting it to hydrothermal carbonization treatment, adding alkaline powder for activation to obtain a biomass carbon fiber carrier, placing the biomass carbon fiber carrier in molten PTFE for pulling and forming to obtain a crude membrane;
[0014] 2) Immersing the crude membrane into the reaction monomer, adding a catalyst, a catalyst ligand, an alkaline powder and a reaction solvent, and heating to obtain a filter material;
[0015] 3) The filter material is folded into a fin structure and then subjected to heat treatment to obtain a folded filter element.
[0016] As a preference,
[0017] Step 1) the biomass material is grapefruit peel white pulp;
[0018] Step 1) The hydrothermal carbonization temperature is 200-230°C and the temperature is kept constant for 5-7 hours.
[0019] As a preference,
[0020] Step 1) The alkaline powder is sodium hydroxide, and the amount used is 0.04-0.10 g / g biomass material.
[0021] As a preference,
[0022] Step 1) When the biomass carbon fiber carrier is placed in molten PTFE for pulling and forming, the pulling stroke is controlled to be 20-30 cm and the pulling speed is 2-3 mm / s.
[0023] As a preference,
[0024] Step 2) The reaction monomers are tris(4-aminophenyl)amine and 3,5-dibromophenylboronic acid in a mass ratio of (0.9-1.2):1, and the amount of the reaction monomers is 3-5 g / g biomass material.
[0025] As a preference,
[0026] Step 2) The catalyst is bis(dibenzylideneacetone)palladium, and the amount used is 0.01-0.03 g / g biomass material;
[0027] Step 2) the catalyst ligand is 2-dicyclohexylphospho-2',4',6'-triisopropylbiphenyl, and its usage is 1.0-1.4 g / g biomass material;
[0028] Step 2) the alkaline powder is sodium hydroxide, and the amount thereof is 0.04-0.06 g / g biomass material;
[0029] Step 2) The reaction solvent is 1,4-dioxane, and the amount used is 3-8 mL / g biomass material.
[0030] As a preference,
[0031] Step 2) The heating temperature is controlled at 90-100°C and maintained at a constant temperature for 46-50 hours.
[0032] As a preference,
[0033] Step 3) The heat treatment temperature is 300-320°C and the temperature is kept constant for 4-6 hours.
[0034] The invention discloses a pleated filter element based on a PTFE modified separation membrane with high efficiency interception.
[0035] In the preparation of previous PTFE filter materials, they are usually attached or deposited on substrates such as paper or non-woven fabrics for composite use. Although the substrate plays a supporting role, the thickness of such substrates is usually small, the supporting material structure is dense but the strength is poor, and the comprehensive performance of the prepared filter material such as porosity, membrane flux, and structural strength is limited by the substrate, resulting in high flow resistance per unit area of the filter material. If the substrate is not resistant to high temperatures, the prepared filter material is not suitable for high temperature environments. When the water content in the dust exceeds 25%, the dust is easy to adhere to the outside of the filter screen, making it difficult to clean, increasing the flow resistance, and causing premature failure and damage, thereby affecting the application of folded filter elements, so modification is required.
[0036] In the technical solution of the present invention, the core lies in the construction of a self-supporting membrane, which improves its structural stability while ensuring rich channels, so that the filter element can be widely used in high temperature and humid environments. In this field, the structural stability is generally enhanced by adding fibers, wherein the biomass fiber has rich and interconnected three-dimensional channels, which can provide abundant attachment space for molten polymer materials, on the one hand, inhibiting the slippage of the PTFE segment, and on the other hand, increasing the film thickness of the PTFE coarse film to a certain extent. The biomass fiber with good self-support can replace the substrate and avoid the limitation of the filter material. Based on renewable biomass, the inventors used chitin, wood fiber and other materials to prepare filter materials and tested them, and found that these materials are not only rigid, but also have the same volume of carbon fiber materials, and the total mass of the grapefruit peel white pulp with a sponge-like three-dimensional structure is reduced by 15 to 20 wt%, and its thickness can reach 1.0 mm or more to prepare ultra-thick filter membranes to increase the upper limit of interception per unit area, in addition, high-density fluid traces can be constructed to reduce the flow resistance of the filter material. The present invention uses the white flesh of grapefruit peel, which is the part without the outer shell layer, has high porosity and good three-dimensional self-supporting effect, can realize the stable and non-leakage of PTFE, that is, can promote the symmetrical and uniform distribution of PTFE on the fiber skeleton, when the folding part of the PTFE filter material produces cracks due to aging, within a period of time, the leakage of PTFE is suppressed to extend the service life of the filter material. In addition, its own flexible structure can enhance the creep property of the filter material and increase the strain range of the filter material, so the folded filter element prepared by the PTFE membrane has great prospects in the field of gas filtration and treatment.
[0037] The present invention removes the cell wall of cellulose by carbonization, and produces a layered structure with many stacked arched layers, which can avoid the mold of the filter material itself and enhance the high temperature applicability of the PTFE filter material. However, direct high temperature carbonization of the filter material will cause the structure to collapse too quickly and embrittle the carbon fiber. The carbon fiber not only presents general carbonization defects, but also easily agglomerates carbon, thereby affecting the comprehensive performance of the filter material. In addition, microwave carbonization is difficult to retain the original sponge-like structure. In order to retain the layered structure after carbonization without losing flexibility, the present invention performs hydrothermal carbonization treatment on the biomass to strengthen the biomass carbon fiber and enhance the controllability of its carbonization process. However, it should be noted that in this process, if an excessively high concentration of concentrated sulfuric acid is used, such as fuming sulfuric acid for high dehydration, the white flesh of the grapefruit peel will also cause obvious structural collapse, resulting in its embrittlement, lamellarization and even direct serious powdering. According to the inventor's experiment, the filter material can be repeatedly wound and bent, and still has high fatigue resistance after 10,000 folds. Biomass carbon fiber is mixed with alkaline powder, and some carbon atoms are separated from the carbon skeleton to form pores. At the same time, the escaping gas forms a large number of pores, which increases the specific surface area of the material.
[0038] Since inorganic biomass carbon fiber is difficult to simply compound with chemically inert PTFE, the present invention impregnates the biomass carbon fiber in molten PTFE to obtain a filter material with small pore size, large specific surface area and good gas permeability. The most important thing is to utilize the characteristics of high-viscosity fluid to steadily pull the biomass carbon fiber upward at a certain speed. The molten PTFE and the biomass carbon fiber move relative to each other, so that the biomass carbon fiber is evenly impregnated, and the interface bonding force between the molten PTFE and the carbon fiber is improved. The impregnation "wire drawing" causes an array structure to appear on the surface of the filter material. Since the array structure plays a buffering role when subjected to force, the local irregular shearing causes the surface of the filter material to form a secondary three-dimensional mesh structure, which further improves the structural stability of the filter material. The internal structure of the carbon fiber is evenly coated, which inhibits the slippage of PTFE, so the impregnation wire drawing can enhance the impact resistance. The degree of impregnation of biomass carbon fiber is affected by the pulling speed. If the pulling speed is too slow, the PTFE continuity will be poor and easy to separate. After the filter material is lifted, the PTFE will sag rapidly. It is only the surface of the biomass carbon fiber that contacts the molten PTFE. The penetration degree of the molten PTFE is suppressed, that is, the degree of infiltration inside the carbon fiber is reduced, and the filter material presents a relatively large brittleness inside. Due to the rapid sag of PTFE, there is no array structure on the surface of the filter material, which also affects the hydrophobicity. The pulling speed is too fast and the PTFE viscosity is too large, the deformation is small, and it is coated on the surface of the carbon fiber. After cooling and hardening, it presents a block shape, which is difficult to achieve "wire drawing", thereby causing the filter material impact resistance to fail to achieve the expected effect. Therefore, in order to enhance the carbon fiber cohesive winding force by impregnation, that is, to enhance the bonding force between carbon fiber and PTFE, avoid carbon fiber peeling, and enhance the structural stability of the filter material at the same time, the present invention should control the pulling speed. After the inventor's experiment, when the pulling speed is controlled at 2-3 mm / s, the filter material is close to complete impregnation, the interface is well bonded, and the mechanical strength is high.
[0039] The present invention further modifies the filter material to have the advantages of low cost and high adsorption capacity. The nanoparticles formed by cross-coupling of tri(4-aminophenyl)amine and 3,5-dibromophenylboronic acid are accumulated into an organic modified layer. If the amount of tri(4-aminophenyl)amine is further increased, the flexible structure causes the long chains to entangle, thereby causing the particles to agglomerate. If the amount of 3,5-dibromophenylboronic acid is increased, the rigidity of the organic modified layer is too large, which in turn embrittles the structure. Therefore, the present invention controls the amount of tri(4-aminophenyl)amine and 3,5-dibromophenylboronic acid to ensure high yield of the reactant. After research by technicians in the field, it can be seen from the characterization that there are CN bonds and BO bonds in the system, indicating that nitrogen atoms and boron atoms have been successfully introduced. Under normal temperature, the inventors constructed an environment with high concentrations of carbon dioxide and sulfur dioxide to characterize the ability of the filter material to adsorb carbon dioxide and sulfur dioxide. As a result, the average carbon dioxide adsorption capacity of the filter material prepared by the present invention exceeded 4 mmol / g, and the average adsorption capacity of sulfur dioxide exceeded 3 mmol / g, while the microporous carbon material only had an adsorption capacity of 2.34 mmol / g for carbon dioxide at 298 K and 1 bar, indicating that the introduction of polar heteroatoms can improve the binding force between the organic modified layer and carbon dioxide, so that the filter material has a certain adsorption capacity. When used in industry, it can more effectively achieve clean discharge of industrial waste gas and reduce particulate pollutants and greenhouse gases. At the same time, the organic modification allows the filter material surface to form a two-dimensional extensible conjugated microporous skeleton, which not only retains abundant nanopores, but also has high flexibility for folding processing.
[0040] The filter material prepared by the present invention not only has nano-level pores, but also has high flexibility and exhibits good resistance to folding fatigue. The rough structure on the surface of the filter material makes it have good water and oil repellency, preventing dust from adhering to the outside of the filter material, thereby increasing the flow resistance and causing premature failure and damage of the filter material. The inventor's experiments show that the organic modified layer exhibits good stability at high temperatures. Therefore, the foldable filter element prepared by the present invention is suitable for high temperature or humid environments, and is particularly suitable for the treatment of high-temperature industrial waste gas.
[0041] The beneficial effects of the present invention are as follows:
[0042] The foldable filter element of the present invention has higher filtration accuracy than existing filter elements. At the same time, the control and optimization of the microstructure enable it to have better resistance to folding fatigue. The large thickness formed enables it to have a higher filtration limit and is not prone to clogging, and the actual service life is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a surface electron microscope characterization image of the folded filter element prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0045] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0046] Unless otherwise specified, the purity of tris(4-aminophenyl)amine used in the examples of the present invention is 97 wt %.
[0047] Unless otherwise specified, the purity of 3,5-dibromophenylboric acid used in the examples of the present invention is 98 wt%.
[0048] Unless otherwise specified, the mass fraction of palladium in the bis(dibenzylideneacetone)palladium used in the embodiments of the present invention is 18-24 wt %.
[0049] Unless otherwise specified, the 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl used in the examples of the present invention has a purity of 95 wt%.
[0050] Unless otherwise specified, the purity of 1,4-dioxane used in the embodiments of the present invention is 99.5 wt %.
[0051] Unless otherwise specified, the purity of N,N-dimethylformamide used in the embodiments of the present invention is 99.5 wt %.
[0052] Unless otherwise specified, the tetrahydrofuran used in the embodiments of the present invention has a purity of 99.5 wt %.
[0053] Example 1: A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, the method comprising:
[0054] 1) 10 g of grapefruit peel was cut into thick slices with a thickness of about 1.5 mm, and then heated to 220 ℃ for 6 h. After adding 0.6 g of NaOH powder for activation, about 4 g of biomass carbon fiber mesh was obtained. The complete 3 g of biomass carbon fiber mesh was cut and immersed in molten PTFE. A stainless steel plate structure was provided on the lower side of the biomass carbon fiber mesh to place the biomass carbon fiber mesh and support it. During traction, the biomass carbon fiber mesh was indirectly pulled by pulling the stainless steel plate. The pulling stroke was controlled to be 25 cm and the pulling speed was 2 mm / s. When the biomass carbon fiber mesh was separated from the molten PTFE, it was quickly cooled by air to obtain a rough membrane.
[0055] 2) The crude membrane was immersed in a reactor containing 6 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, and 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added. The reactants were stirred under a nitrogen atmosphere and kept at a constant temperature of 100 °C for 48 h. The product was washed with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dried to obtain a filter material;
[0056] 3) After the filter material is folded into a fin structure, it is kept at a constant temperature of 300 °C for 6 h in an air atmosphere, and then cooled to obtain a folded filter element.
[0057] The filter material and filter element obtained in this example were subjected to performance testing, and the performance test is as follows.
[0058] 1. Aperture test:
[0059] The pore sizes of 20 test pores on the filter element were measured and recorded using a fully automatic specific surface and pore size analyzer V-Sorb X800 (SM).
[0060] 2. Filter element flow test:
[0061] A YG461-III air permeability meter was used to characterize the average air permeability rate of the air flow through the filter element per unit time under a pressure of 130 Pa. The experiment was continued for 30 days. The average air permeability rate of the air flow through the filter element was measured after the filter element had been running for 30 days. The result was expressed in mm / s.
[0062] 3. Pressure difference test:
[0063] Referring to the national standard GB / T6223-1997 test method, start the vacuum pump, pass the test model without filter at a flow rate of 25 L / min, and measure the system resistance P1 of the inspection device. Pass the test model with filter at a flow rate of 25 L / min, and measure the system resistance P2. P2-P1 is the pressure difference formed by the vacuum, and the result is expressed in Pa.
[0064] 4. Retention rate test:
[0065] The TSI8130 filter tester is used to detect the retention rate of the filter element for PM2.5 particles. A fixed volume of air containing PM2.5 particles is extracted at a constant rate, and the retention rate is calculated by measuring the attenuation of the particles.
[0066] 5. Anti-folding fatigue test:
[0067] The filter material is fatigue tested by using the MIT folding endurance tester. The filter material is bent 1000 times to observe whether the filter material is cracked. If there is no cracking, it is recorded as PASS, otherwise it is recorded as FAIL.
[0068] 6. Tensile test:
[0069] The filter material was loaded by a Zwick biaxial tensile testing machine, the load-strain curve of the filter material was measured, and the elastic modulus and elongation at break of the filter material were calculated.
[0070] 7. Greenhouse gas adsorption:
[0071] In a closed environment, a carbon dioxide-nitrogen mixed gas and a sulfur dioxide-nitrogen mixed gas with a concentration of 20 mmol / g were released and passed through the filter material. After 48 hours, the concentrations of carbon dioxide and sulfur dioxide in the environment were measured, and the adsorption amount was calculated based on the ambient gas concentration and the mass of the filter material.
[0072] The results are as follows.
[0073] According to the results in the above table, it can be seen that the present invention successfully realizes a filter element with small pore size, low flow resistance and high retention rate, wherein the filter material can be repeatedly wound and bent, and still has high fatigue resistance after 10,000 folds. Compared with pure PTFE membrane, the filter material obtained by the present invention has high flexibility and higher adsorption capacity than microporous carbon material. The filter element prepared by the present invention can filter out 96% of ultrafine dust while retaining a low filtration pressure difference. Compared with conventional PTFE filter elements, the air permeability of the present invention is increased by 50-70%. It can be seen that the filter element prepared by the present invention has a good prospect for gas purification.
[0074] Example 2: A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, the method comprising:
[0075] 1) 10 g of grapefruit peel was cut into thick slices with a thickness of about 1.5 mm, and then heated to 220 ℃ for 6 h. After adding 0.6 g of NaOH powder for activation, about 4 g of biomass carbon fiber mesh was obtained. The complete 3 g of biomass carbon fiber mesh was cut and immersed in molten PTFE. A stainless steel plate structure was provided on the lower side of the biomass carbon fiber mesh to place the biomass carbon fiber mesh and support it. During traction, the biomass carbon fiber mesh was indirectly pulled by pulling the stainless steel plate. The pulling stroke was controlled to be 25 cm and the pulling speed was 2.5 mm / s. When the biomass carbon fiber mesh was separated from the molten PTFE, it was quickly cooled by air to obtain a rough membrane.
[0076] 2) The crude membrane was immersed in a reactor containing 6 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, and 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added. The reactants were stirred under a nitrogen atmosphere and kept at a constant temperature of 100 °C for 48 h. The product was washed with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dried to obtain a filter material;
[0077] 3) After the filter material is folded into a fin structure, it is kept at a constant temperature of 300 °C for 6 h in an air atmosphere, and then cooled to obtain a folded filter element.
[0078] The filter material and filter element obtained in this example were subjected to performance testing, and the results are as follows.
[0079] According to the results in the above table, this example obtained a filter element with small pore size, low flow resistance, high flexibility, and folding fatigue resistance. This example accelerated the speed of pulling the biomass carbon fiber net. Since the molten PTFE has high viscosity, the biomass carbon fiber is pulled upward steadily at an appropriate speed, which can not only achieve uniform impregnation of the biomass carbon fiber, but also improve the interface bonding force between the molten PTFE and the carbon fiber, and also obtain an ordered array structure. Since the array structure plays a buffering role when subjected to force, and the local irregular shearing makes the filter surface form a secondary three-dimensional network structure, the structural stability of the filter material is significantly improved. In addition, the internal structure of the carbon fiber is evenly coated, which inhibits the slippage of PTFE, thereby enhancing the impact resistance of the filter material.
[0080] In addition, in order to verify the stability of the structure, the folded filter element prepared in this example was subjected to the folding fatigue test and SEM characterization was performed. The characterization results are shown in the figure. Figure 1 As shown, from Figure 1It can be clearly seen that the folded filter element prepared in this example did have a microstructural fracture during the folding process, but no obvious structural collapse occurred, the loss rate was low, and no cracks appeared from macroscopic observation, which shows that the folded filter element of the present invention has extremely excellent microstructural stability. Higher microstructural stability can ensure that during use, the filter element can still retain its filtering performance well even if it is repeatedly folded or impacted, and it also has good anti-folding fatigue ability at the microscopic level.
[0081] Example 3: A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, the method comprising:
[0082] 1) 10 g of grapefruit peel was cut into thick slices with a thickness of about 1.5 mm, and then heated to 220 ℃ for 6 h. After adding 0.6 g of NaOH powder for activation, about 4 g of biomass carbon fiber mesh was obtained. The complete 3 g of biomass carbon fiber mesh was cut and immersed in molten PTFE. A stainless steel plate structure was provided on the lower side of the biomass carbon fiber mesh to place the biomass carbon fiber mesh and support it. During traction, the biomass carbon fiber mesh was indirectly pulled by pulling the stainless steel plate. The pulling stroke was controlled to be 25 cm and the pulling speed was 3.0 mm / s. When the biomass carbon fiber mesh was separated from the molten PTFE, it was quickly cooled by air to obtain a rough membrane.
[0083] 2) The crude membrane was immersed in a reactor containing 6 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, and 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added. The reactants were stirred under a nitrogen atmosphere and kept at a constant temperature of 100 °C for 48 h. The product was washed with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dried to obtain a filter material;
[0084] 3) After the filter material is folded into a fin structure, it is kept at a constant temperature of 300 °C for 6 h in an air atmosphere, and then cooled to obtain a folded filter element.
[0085] The filter material and filter element obtained in this example were subjected to performance testing, and the results are as follows.
[0086] According to the results in the above table, this example further accelerated the speed of pulling the biomass carbon fiber net. It can be seen that its flexibility has dropped significantly. Due to the faster speed, the viscosity of PTFE will increase and the deformation will decrease, so that the PTFE coated on the surface of the carbon fiber will be in block shape after cooling and hardening, which makes it difficult to achieve "wire drawing", resulting in a significant decrease in the mechanical properties of the filter material and the adsorption performance of greenhouse gases. On the other hand, when the researchers further increased the pulling speed to 3.5 mm / s on this basis, the biomass carbon fiber net showed obvious macroscopic collapse during the traction process, macroscopic pits appeared on the surface, and the edge structure collapsed seriously. It can be seen that too fast pulling will exceed the structural strength of the biomass carbon fiber net. When the researchers reduced the pulling speed to 1.5 mm / s, they found that the actual PTFE load rate was extremely low, resulting in a large amount of melt flow dripping. Therefore, based on the current test results, the best pulling speed is still 2-3 mm / s.
[0087] Comparative Example 1: 1) 10 g of grapefruit peel white pulp was cut into thick slices of about 1.5 mm thick, then heated to 220 ° C and kept at a constant temperature for 6 h, and 0.6 g of NaOH powder was added for activation to obtain about 4 g of biomass carbon fiber mesh, and 3 g of the complete biomass carbon fiber mesh was cut and immersed in molten PTFE. A stainless steel plate structure was provided on the lower side of the biomass carbon fiber mesh for placing the biomass carbon fiber mesh and supporting it. During traction, the biomass carbon fiber mesh was indirectly pulled by pulling the stainless steel plate. The pulling stroke was controlled to be 25 cm, and the pulling speed was 2.5 mm / s. When the biomass carbon fiber mesh was separated from the molten PTFE, it was quickly cooled by air to obtain a rough membrane;
[0088] 2) The crude membrane was immersed in a reactor containing 4 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, and 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added. The reactants were stirred under a nitrogen atmosphere and kept at a constant temperature of 100 °C for 48 h. The product was washed with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dried to obtain a filter material;
[0089] 3) After the filter material is folded into a fin structure, it is kept at a constant temperature of 300 °C for 6 h in an air atmosphere, and then cooled to obtain a folded filter element.
[0090] The filter material and filter element obtained in this example were subjected to performance testing, and the results are as follows.
[0091] According to the results in the above table, this example reduces the ratio of the reaction monomers, that is, reduces the amount of tri(4-aminophenyl)amine, which makes the organic modified layer too rigid, resulting in structural brittleness. Compared with Example 2, the filter material has poor flexibility and low impact resistance. After 30 days, the average air permeability rate is greatly reduced. When folded about 780 times, obvious fine cracks appear on the filter material, indicating that the excessive rigidity of the filter material affects the structural stability.
[0092] Comparative Example 2: A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, the method comprising:
[0093] 1) Take 10 g of tree trunk phloem layer and cut it into thick sheets of about 1.5 mm thick. Then heat it to 220 ℃ and keep it constant for 6 h. After adding 0.6 g of NaOH powder for activation, about 5 g of biomass carbon fiber net is obtained. The complete 3 g of biomass carbon fiber net is cut and immersed in molten PTFE. A stainless steel plate structure is provided on the lower side of the biomass carbon fiber net to place the biomass carbon fiber net and support it. When pulling, the biomass carbon fiber net is indirectly pulled by pulling the stainless steel plate. The pulling stroke is controlled to be 25 cm and the pulling speed is 2.5 mm / s. When the biomass carbon fiber net is separated from the molten PTFE, it is quickly cooled by air to obtain a rough film.
[0094] 2) Immerse the crude membrane in a reactor containing 6 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, add 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane, stir the reactants under a nitrogen atmosphere, keep the temperature at 100 °C for 48 h, wash the product with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dry to obtain a filter material;
[0095] 3) Keep the filter material at a constant temperature of 300 °C for 6 h in an air atmosphere. After cooling, stick the filter material on paper and fold the filter material in sequence to obtain a folded filter element.
[0096] The filter material and filter element obtained in this example were subjected to performance testing, and the results are as follows.
[0097] According to the results in the above table, in this example, the bast layer of the tree trunk is used to prepare the biomass carbon fiber mesh. Although its axial channels are arranged more closely, ensuring a higher air permeability rate, its structure is mainly externally tough and relatively simple. Compared with Example 2, the filter material prepared in this example is not resistant to folding fatigue, and obvious cracks appear after about 700 folds. Moreover, after using the filter element for 30 days, its air permeability rate is greatly reduced, making it difficult to ensure the long-term effect of the filter element.
[0098] Comparative Example 3: A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, the method comprising:
[0099] 1) 10 g of grapefruit peel white pulp was cut into thick slices with a thickness of about 1.5 mm, and then heated to 600 ℃ and kept at this temperature for 2 h to obtain about 3.5 g of biomass carbon fiber net. The complete 3 g of biomass carbon fiber net was cut and immersed in molten PTFE. A stainless steel plate structure was provided on the lower side of the biomass carbon fiber net to place the biomass carbon fiber net and support it. During traction, the biomass carbon fiber net was indirectly pulled by pulling the stainless steel plate. The pulling stroke was controlled to be 25 cm and the pulling speed was 2.5 mm / s. When the biomass carbon fiber net was separated from the molten PTFE, it was quickly cooled by air to obtain a rough membrane.
[0100] 2) The crude membrane was immersed in a reactor containing 6 g of tris(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboronic acid, and 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added. The reactants were stirred under a nitrogen atmosphere and kept at a constant temperature of 100 °C for 48 h. The product was washed with pure water, N,N-dimethylformamide and tetrahydrofuran, respectively, and dried to obtain a filter material;
[0101] 3) After the filter material is folded into a fin structure, it is kept at a constant temperature of 300 °C for 6 h in an air atmosphere, and then cooled to obtain a folded filter element.
[0102] The filter material and filter element obtained in this example were subjected to performance testing, and the results are as follows.
[0103] According to the results in the above table, the white pulp of grapefruit peel was carbonized at high temperature in this case. Compared with hydrothermal carbonization, although the specific surface area of biomass carbon fiber in this case increased, the carbon conversion rate was low and the porosity was only 85%. The structure collapsed or brittle too quickly during high temperature treatment, which not only showed general carbonization defects, but also led to poor structural stability and a rapid decrease in permeability after 30 days in the air permeability test. Carbon agglomeration also occurred easily, thus affecting the comprehensive performance of the filter material. The hemicellulose in the biomass carbon fiber was completely decomposed, and the carbon free radicals formed by cellulose were rearranged and crystallized. At a high temperature of 600 ℃, its structure showed instability.
[0104] Comparative Example 4: Commercially available pleated filter element based on hydrophobic PTFE filter material.
[0105] The filter material and filter element in this example were tested for performance, and the results are as follows.
[0106] According to the results in the above table, the filtering accuracy and carbon dioxide adsorption performance of the commercially available filter element are not as good as those of the filter element prepared by the present invention, the flow resistance is large, and the average air permeability rate is significantly reduced after 30 days, indicating that its structural stability is poor and the filter material flexibility is poor. After folding the filter material of this example 1000 times, obvious cracks appeared at the folding part, and its service life is relatively short. It can be seen from this that the filter element prepared by the present invention has a good prospect in the field of gas filtration.
Claims
1. A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception, characterized in that: The method comprises: 1) taking a biomass material and subjecting it to hydrothermal carbonization treatment, adding alkaline powder for activation to obtain a biomass carbon fiber carrier, placing the biomass carbon fiber carrier in molten PTFE for pulling and forming to obtain a crude membrane; 2) Immersing the crude membrane into the reaction monomer, adding a catalyst, a catalyst ligand, an alkaline powder and a reaction solvent, and heating to obtain a filter material; 3) Folding the filter material into a fin structure and then heating it to obtain a folded filter element; Step 1) the biomass material is grapefruit peel white pulp; Step 2) The reaction monomers are tri(4-aminophenyl)amine and 3,5-dibromophenylboric acid. The crude membrane prepared from 3 g of biomass carbon fiber carrier is immersed in 6 g of tri(4-aminophenyl)amine and 5 g of 3,5-dibromophenylboric acid.
2. The method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, characterized in that: Step 1) The hydrothermal carbonization temperature is 200-230°C and the temperature is kept constant for 5-7 hours.
3. The method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, characterized in that: Step 1) The alkaline powder is sodium hydroxide, and the amount used is 0.04-0.10 g / g biomass material.
4. A method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, 2 or 3, characterized in that: Step 1) When the biomass carbon fiber carrier is placed in molten PTFE for pulling and forming, the pulling stroke is controlled to be 20-30 cm and the pulling speed is 2-3 mm / s.
5. The method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, characterized in that: Step 2) The heating temperature is controlled at 90-100°C and maintained at a constant temperature for 46-50 hours.
6. The method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, characterized in that: Step 3) The heat treatment temperature is 300-320°C and the temperature is kept constant for 4-6 hours.
7. The method for preparing a folded filter element based on a PTFE modified separation membrane with high efficiency interception according to claim 1, characterized in that: Step 2) the catalyst is bis(dibenzylideneacetone)palladium, the catalyst ligand is 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, the alkaline powder is sodium hydroxide, and the reaction solvent is 1,4-dioxane; For every 3 g of crude membrane prepared from the biomass carbon fiber support, 0.2 g of bis(dibenzylideneacetone)palladium, 0.2 g of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.5 g of NaOH powder and 60 mL of 1,4-dioxane were added.
8. A folded filter element based on a PTFE modified separation membrane with high efficiency interception obtained by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Folded teflon composite microporous membrane and filter element
CN101961607A
Method for preparing coal-based composite carbon membrane from recombination family components
CN102125810A
Preparation method and application of Pd / C3N4@biomass carbon fiber composite film
CN108636136A